2009
DOI: 10.1177/0143831x09351215
|View full text |Cite
|
Sign up to set email alerts
|

Welcome to the House of Fun: Work Space and Social Identity

Abstract: Following the diffusion of HRM as the dominant legitimating managerial ideology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 48 publications
(77 reference statements)
1
48
0
Order By: Relevance
“…Organizations and employers also manipulate workers' identity through materiality (Harding 2002;Kunda 1992), which can be interpreted as a form of managerial control (e.g., Kärreman and Alvesson 2004), even extending it to the level of everyday life (Hancock and Tyler 2004) and enhancing the 'fun' factor of work (Baldry and Hallier 2010); the latter being an example of how work space is designed to support a range of officially encouraged 'fun' activities at work. The critical perspective in the present study addresses the taken-forgranted and unnoticed effects of materiality on identity.…”
Section: Materiality and Identitymentioning
confidence: 99%
“…Organizations and employers also manipulate workers' identity through materiality (Harding 2002;Kunda 1992), which can be interpreted as a form of managerial control (e.g., Kärreman and Alvesson 2004), even extending it to the level of everyday life (Hancock and Tyler 2004) and enhancing the 'fun' factor of work (Baldry and Hallier 2010); the latter being an example of how work space is designed to support a range of officially encouraged 'fun' activities at work. The critical perspective in the present study addresses the taken-forgranted and unnoticed effects of materiality on identity.…”
Section: Materiality and Identitymentioning
confidence: 99%
“…It is important to note that a lack of power within first‐line management positions is not confined to nursing roles (Kanter 1977) as studies of physical office space and office resources, reported in business and management literature, have yielded some interesting insights into physical work space and links with the observable symbols that suggest status, power and authority. For example, Baldry and Hallier (2010) note that workspaces are not merely containers to house work processes, rather they are powerful symbols of organizational culture and identity. Similarly, Panayiotou and Kafiris (2011)suggest that workspaces shape and communicate our identity and affirm our status within the organization.…”
Section: Workpaces Power and Statusmentioning
confidence: 99%
“…The production of "fun" in the call centre is a common theme and its end is always towards the worker's acceptance of the corporeal conditions of work. 86 With the caveats regarding variations in call centre labour processes in mind, the compulsion of stylised worker-customer interactions that engage the affective, emotional and aesthetic capabilities of bodies is a general one. 87 Compulsion is articulated through managerial/technological methods such as the monitoring and scoring of calls against targets that include objective measures such as compliance with scripted portions of calls and the regulation of behaviours such as the pace and pitch of speech.…”
Section: Body Work and Political Potentialitymentioning
confidence: 99%